Natural nanogold - Osovetsky, Boris (Springer, 2017)
This book summarizes systematic data on nanogold in geological objects, including mineral-concentrators of nanogold, and the structure and chemical composition of nanogold aggregates. The book also discusses problems that arise during the development of nanogold resources and provides recommendations for prospering new gold deposits with thin-dispersed gold. Electronic microphotos and microprobe analyses support this comprehensive overview of the genesis of nanogold. The book especially focuses on the genesis of nanogold, the processes of nanogold concentration in natural environments, and geological formations containing nanogold.
Keywords: Nanostructured materials.; Gold.; elektronické knihy; electronic books